Counting on Indigenous accountants: Collaborative curriculum development for an Indigenous pre-accounting enabling program - Hill, Guzyal; Wegner, Aggie; Low , David (The Australian Journal of Indigenous Education, 2022)
With less than 100 registered Indigenous accountants in Australia compared to an estimated 200,000 non-Indigenous people in the field, there is serious underrepresentation of the Indigenous population in the profession. There are many imperatives for increasing the number of Aboriginal people in accounting, but the barriers that individuals face before or upon entering the field are formidable. Therefore, the development of enabling programs in higher education is essential. The objective of this research is to develop a curriculum for the Indigenous Pre-Accounting Enabling Program at Charles Darwin University (CDU) in Darwin, Australia that is culturally empowering, breaks down the barriers for entering university, motivates Indigenous students to study accounting, links students to Indigenous professionals, offer gateways into the industry, and establishes a community of Indigenous students online and on campus. The novelty of the program is its early involvement of Indigenous accountants as role models as well as Indigenous corporations, regulators of Indigenous businesses (such as the Office of the Registrar of Indigenous Corporations) and accreditation bodies such as the Chartered Professional Accountants and Chartered Accountants.